Character Education Values In The Character Of Puntadewa In Wayang Kulit Art - Utomo, Fajar Wahyudi; Triyuono, Arif (Jurnal Multidisiplin Sahombu, 2024)
Wayang Kulit /Shadow puppetry is one of the arts of Central Javanese society which does not only contain elements of entertainment. More than that, Wayang Kulit hold many philosophical values of life, including character education. The value of character education in Wayang Kulit art is contained in every character who plays a role in it. This research aims to analyze the value of character education in one of the Wayang Kulit characters, namely Puntadewa. Puntadewa is one of the members of the Pandawa (Yudistira/Puntadewa, Bima, Arjuna, Nakula, Sadewa) who are famous in the world of Wayang. The method in this research is descriptive qualitative using library research. The results of this study explain that there are character education values in the Puntadewa character, including being big-hearted, sincere, honest, fair, impartial, and simple. These character education values are positive examples which can then be used as examples for students. Instilling character education values in the character Puntadewa is something that can be done by teachers using various methods.